Melanoma cellular plasticity - Novak, Daniel; Utikal, Jochen (International journal of molecular sciences, 2022)
Despite the advances of modern medicine and the development of innovative and promising new therapeutic strategies for the treatment of the numerous types of cancer, far too many patients still lose the battle against these devastating diseases [...]
Gesehen am 05.02.2024
Dieser Artikel gehört zum Special issue: Melanoma cellular plasticity